Growth patterns and responses to climate variability of Subantarctic Pilgerodendron uviferum forests in the Aysen (∼47-48°S) and Magallanes (∼53°S) regions, southern Patagonia - Aguilera-Betti, Isabella; Aravena Donaire, Juan Carlos; Villalba, Ricardo; Gonzalez-Reyes, Alvaro; Fernandez-Garcia, Catalina; Bringas, Christian (My University, 2025)
The temperate forests of southern Chile are unique and complex ecosystems, threatened by climate change and anthropogenic activities. One of the long-lived and endemic species of these forests is the Guaitecas Cypress (Pilgerodendron uviferum), the southernmost conifer in the world, with a latitudinal distribution between 39 and 55 degrees S, from temperate rainy to Subantarctic climates, being an ideal model for studying the response of tree species to climate in high latitudes. The objective of this study is to determine the growth patterns of P. uviferum forests in Chilean regions of Aysen (similar to 47-48 degrees S) and Magallanes (similar to 53 degrees S) using ring-width chronologies of four and six forests in Aysen and Magallanes, respectively. A Principal Component Analysis identified two dominant patterns: PC1 associated with Magallanes chronologies, and PC2 with Aysen chronologies. Using ERA5-Land data (1979-2020), both components showed positive correlations with precipitation and negative correlations with temperature. PC1 was positively related to soil water content, while PC2 negatively. Contrasting responses were found with large-scale forcings, where PC1 was negatively correlated with AAO and PDO, and positively correlated with SOI, while PC2 showed the opposite pattern. Spectral analyses reinforce these results, showing regional differences in the growth patterns of P. uviferum. This opposite relationship suggests that regional growth patterns of P. uviferum are influenced by large-scale modes of climate variability affecting southern South American climates. These results highlight the potential of P. uviferum chronologies to represent the large-scale climate variability of southern South America and to recover the low-frequency signal in climate reconstructions from this species.
Keywords: pilgerodendron uviferum; growth patterns; climate variability; subantarctic forests